Transforming fallow lands: An impact evaluation of the Comprehensive Rice Fallow Management (CRFM) Program in Odisha - Roy, Devesh; Padhee, Arabinda Kumar; Pradhan, Mamata; Saroj, Sunil; Vidhani, Vandana; Kumar, Devendra; Kumar Burman, Amit (International Food Policy Research Institute, 2025)
The Comprehensive Rice Fallow Management (CRFM) program, initiated by the Department of Agriculture & Farmers’ Empowerment (DAFE), Government of Odisha, is a program to address the underutilization of rice fallow lands in Odisha, particularly during the Rabi (post-monsoon) season which occurs following the Kharif (monsoon) paddy harvest. CRFM was implemented to encourage cultivation of pulses and oilseeds that thrive on residual soil moisture. The CRFM program was implemented in 20 districts of Odisha, in collaboration with the Consultative Group on International Agricultural Research (CGIAR) and the Indian Council of Agricultural Research (ICAR), Government of India empaneled agencies that have a presence in the state and prior experience in similar programs. In the remaining 10 districts of the state, the CRFM program was implemented by the state government’s Chief District Agriculture Officers (CDAOs). The impacts of CRFM interventions evaluated in this study comprise crop demonstrations organized in clusters of at least 20 hectares, with crops like black gram, green gram, chickpeas, lentils, grass peas, sesamum, and mustard.